2017
DOI: 10.1155/2017/5893123
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Surfactin and Fengycin Production byBacillus mojavensisA21: Application for Diesel Biodegradation

Abstract: This work concerns the study of the enhancement of surfactin and fengycin production by B. mojavensis A21 and application of the produced product in diesel biodegradation. The influences of the culture medium and cells immobilization were studied. The highest lipopeptides production was achieved after 72 hours of incubation in a culture medium containing 30 g/L glucose as carbon source and a combination of yeast extract (1 g/L) and glutamic acid (5 g/L) as nitrogen sources with initial pH 7.0 at 30°C and 90% v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 41 publications
(52 reference statements)
6
25
0
5
Order By: Relevance
“…La liberación de biosurfactantes es una de las estrategias utilizadas por los microorganismos para influir en la absorción de hidrocarburos y compuestos hidrofóbicos en general (Johnsen et al 2005, Chong & Li, 2017; debido a que la estructura de los biosurfactantes permite solubilizar los hidrocarburos y con esto hacerlos disponibles para la degradación (Nievas et al, 2008, Hmidet et al, 2017. A pesar de obtener crecimiento de cada una de los 17 biotipos de Azospirillum brasilense en medio base sangre, ninguna de ellas presentó beta hemolisis.…”
Section: Discussionunclassified
“…La liberación de biosurfactantes es una de las estrategias utilizadas por los microorganismos para influir en la absorción de hidrocarburos y compuestos hidrofóbicos en general (Johnsen et al 2005, Chong & Li, 2017; debido a que la estructura de los biosurfactantes permite solubilizar los hidrocarburos y con esto hacerlos disponibles para la degradación (Nievas et al, 2008, Hmidet et al, 2017. A pesar de obtener crecimiento de cada una de los 17 biotipos de Azospirillum brasilense en medio base sangre, ninguna de ellas presentó beta hemolisis.…”
Section: Discussionunclassified
“…Effect of aeration on biosurfactant was assayed by lling different volume of media in 250 ml asks and it was observed that 40 % of aeration (100 ml media in 250 ml ask) was most suitable (E24% = 47.41 ± 1.62%), which followed by 30 % (E24% = 38.00 ± 2.30%) and 20% (E24% = 27.825 ± 1.73%) ( Fig.2(a)). Bacillus mojavensis A21 produced highest surfactin when cultured in 10% ask (25 ml media in 250 ml of ask) while the production in decreased when culture was kept in 70% aeration ( 75 ml media in 250 ml ask) (Hmidet et al 2017). Bacillus subtilis BS5 produced maximum surfactin 10% media containing ask where as production is decline sharply when media volume was increased from 10% (Abdel-mawgoud et al 2008).…”
Section: Ofat Analysismentioning
confidence: 99%
“…Biosurfactant release is a metabolic strategy used by microorganisms in the adsorption of hydrocarbons and hydrophobic compounds in general (Johnsen et al 2005, Chong andLi 2017). It facilitates hydrocarbon degradation (Hmidet et al 2017, Nievas et al 2008. Numerous bacteria, such as Pseudomonas sp.…”
Section: Introductionmentioning
confidence: 99%
“…(Liu et al 2019), and Bacillus sp. (Hmidet et al 2017) degrade xenobiotics; however, since many are potential human pathogens, they can represent a health risks, making their use complicated.…”
Section: Introductionmentioning
confidence: 99%